Case Report: Two cases of IgG4-related kidney disease with monoclonal gammopathy - Dong, Qian; Tang, Xuanli; Liu, Jiang; Xu, Pengjie (Frontiers in Immunology, 2025)
IntroductionIgG4-related disease (IgG4-RD) is a newly classified but poorly understood immune-medicated systemic disease. Monoclonal gammopathy encompasses a spectrum of disorders driven by clonal plasma cell proliferation, leading to the presence of monoclonal immunoglobulins (M-proteins) in serum or urine. IgG4-related nephropathy with associated monoclonal gammopathy is rare, and its etiology is poorly understood.Case presentationThis article reports two rare cases of IgG4-related kidney disease combined with monoclonal gammopathy. Case 1 was a 69-year-old male presented with renal insufficiency and mild proteinuria, along with significant elevations of IgG, IgG4, eosinophils, and IgE, and severe reductions in complement C3 and C4. Serum free light chains κ and λ levels were elevated, monoclonal IgG-λ protein was detected, and lymphadenopathy was observed. Renal biopsy revealed multi-focal and flaky storiform fibrosis. In the renal interstitium, IgG4-positive cells >10/high-power field (HPF), IgG4/IgG >40%. Interstitial inflammatory cells κ were scattered weakly positive, and λ was diffuse strong positive. Bone marrow aspiration did not show obvious plasmablast or abnormal plasma cell clones, but eosinophils were significantly elevated. Case 2 was a 71-year-old male who presented with renal insufficiency and massive proteinuria, along with elevated IgG and IgG4 levels. Serum free light chain κ and λ were elevated, and monoclonal IgM-κ was identified. PLA2R testing was negative. Renal biopsy revealed secondary membranous nephropathy (SMN) without evidence of monoclonal renal injury. Bone marrow aspiration showed evident eosinophils, mature plasma cells accounted for 3.5% and no express light chain restriction.ConclusionsCase 1 was diagnosed with IgG4-TIN combined with MGRS, which showed significant renal and hematological improvement after corticosteroid therapy. Case 2 was diagnosed as secondary membranous nephropathy combined with MGUS, but IgG4-MN cannot be ruled out. His renal function improved with methylprednisolone and rituximab treatment, but the M-protein persisted. We review the related diagnosis and treatment to provide more information for clinical practice.